Legal Positivism, Rule of Law and Freedom: A Proposal for Formulating - Arias Castillo, Tomás A.; Herrera Orellana, Luis Alfonso (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This article explores possible connections between legal positivism, classical liberalism and the rule of law, a task that has been obstructed by the anti-positivist vision of liberal authors. In that sense, anti-positivists critics are analyzed and contested with the purpose of showing the compatibility between legal positivism and the rule of law ideal.